Reference Value for the Distance Walked in the Six-Minute Walk Test in Obese Brazilian Men in the Preoperative Period of Bariatric Surgery - Cesar Antonio Luchesa; Thiago Thomaz Mafort; Rafael Rodrigues da Silva; Isabela Cristina Paro; Fernanda Micheli de Souza; Agnaldo José Lopes (Journal of Obesity)
Background. Obesity has several effects on the mechanics of the rib cage that may impair the exercise performance of obese individuals and therefore impact the assessment of surgical risk. This study aimed to establish a reference value for the 6-minute walk distance (6 MWD) in obese Brazilian men in the preoperative period of bariatric surgery that considers the effect of lung function. Methods. This was a cross-sectional study in which 104 obese men underwent the six-minute walk test (6 MWT) before bariatric surgery. They also underwent the spirometry test and respiratory muscle strength measurement before the 6 MWT. Results. The 6 MWD was correlated with age (r = −0.388, p=0.0005), weight (r = −0.365, p=0.0007), height (r = 0.285, p=0.022), body mass index (BMI) (r = −0.543, p<0.0001), forced vital capacity (FVC) (r = 0.472, p<0.0001), peak expiratory flow (r = 0.253, p=0.031), and maximal inspiratory pressure (r = 0.313, p=0.017). In the stepwise forward regression analysis, BMI, FVC, and age were the only variables that independently predicted the 6 MWD and explained 40% of its variability. The reference equation proposed for obese Brazilian men is 6 MWD (m) = 570.5 − (3.984 × BMIkg/m2) + (1.093 × FVC%predicted) − (0.836 × ageyrs). Conclusion. In this sample of obese Brazilian men, lung function contributed to poor performance in the 6 MWT. In these individuals, BMI, FVC, and age were the variables that composed the reference equation for the 6 MWD. Thus, in several clinical settings, such as in the evaluation before bariatric surgery, pulmonary function data are important to determine the reference value for the 6 MWD.